1984
DOI: 10.3382/ps.0632285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parathyroid Hormone on Total Phosphate and Inorganic Phosphate in Blood, Plasma, and Urine of Domestic Fowl

Abstract: Previous work has shown that parathyroid hormone causes the kidneys of domestic fowl to secrete inorganic phosphate (Pi) into the urine. Secreted Pi is not derived directly from plasma Pi. The objective of the present study was to determine if direct or indirect correlations exist between the urinary Pi excretion rate and the concentration of phosphate in plasma or whole blood. Parathyroid hormone dissolved in gelatin carrier vehicle was injected into immature domestic fowl to cause net renal Pi secretion. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Namely, while certain authors observed morphological changes indicative of parathyroid hyperplasia or hypertrophy (Reece and Frazier, 1990), in this study we found regressive changes, vacuolar degeneration and fibrosis suggestive of hypofunction, at least up to 2 weeks of age of the infected experimental chickens. The increased phosphate excretion caused, even though indirectly, by enhanced parathyroid hormone secretion presumably associated with parathyroid hyperplasia (Klinefelter et al, 1984) may Acta Veterinaria Hungarica 47, 1999 be one of the possible explanations of the decreased phosphate levels of the blood plasma. At the same time, the parathyroid damage seen by us is indicative of a decreased parathyroid hormone secretion and is inconsistent with the existence of the above-mentioned correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, while certain authors observed morphological changes indicative of parathyroid hyperplasia or hypertrophy (Reece and Frazier, 1990), in this study we found regressive changes, vacuolar degeneration and fibrosis suggestive of hypofunction, at least up to 2 weeks of age of the infected experimental chickens. The increased phosphate excretion caused, even though indirectly, by enhanced parathyroid hormone secretion presumably associated with parathyroid hyperplasia (Klinefelter et al, 1984) may Acta Veterinaria Hungarica 47, 1999 be one of the possible explanations of the decreased phosphate levels of the blood plasma. At the same time, the parathyroid damage seen by us is indicative of a decreased parathyroid hormone secretion and is inconsistent with the existence of the above-mentioned correlation.…”
Section: Discussionmentioning
confidence: 99%